Isolation and identification of endophytic fungi from Alhagi sparsifolia Shap. and their antibacterial activity - Mayila Tuerdibieke; Xue Tian; Xuerui An; Yaping Feng; Wei Liu (Heliyon, 2024)
In order to explore the endophytic resources of Alhagi sparsifolia Shap. and identified novel antibacterial substances. Thirty endophytic fungal strains were isolated from the stems and roots of A. sparsifolia Shap. Morphological and molecular biology methods were used to identify ten strains of fungi, including four strains of Aspergillus niger, three strains of Alternaria alternata, two strains of Aspergillus flavus, and one strain of Fusarium incarnatum. All these strains were isolated from A. sparsifolia Shap. for the first time, and of these Aspergillus was the dominant genus. Antibacterial activity of the ten strains against Escherichia coli, Staphylococcus aureus, Candida albicans, and Pseudomonas aeruginosa were evaluated using the disc diffusion method. The results demonstrated that the metabolites from all the strains had inhibitory effects on at least one indicator bacterium. Notably, the endophytic fungi AFJ3 and AFG6 demonstrated strong broad-spectrum antibacterial activity, particularly against E. coli, with inhibition zones measuring 32.0 ± 0.3 and 31.3 ± 0.3 mm, respectively. The three endophytic fungi (AFG1, AFG2, and AFG3) isolated from the roots demonstrated significant antibacterial activity against P. aeruginosa forming an inhibition zone of diameter 31.3 ± 0.1, 25.6 ± 0.2, and 25.6 ± 0.2 mm, respectively. However, the strains of endophytic fungi demonstrated no significant inhibitory effects on C. albicans. Ultra-high performance liquid chromatography with quadrupole time-of-flight mass spectrometry/mass spectrometry (UPLC-QTOF-MS/MS) analysis depicted that the ethyl acetate phase of AFJ3 and AFG6 fermentation broth predominantly contained organic acids, phenolic acids, flavonoids, and fatty acids. These secondary metabolites often exhibited good antibacterial activity. This study broadens our understanding of endophytic fungi in A. sparsifolia Shap. The antibacterial activity of some strains of endophytic fungi was significant, making it worthy of further research on their active material.